2022
DOI: 10.1109/ojsp.2022.3229618
|View full text |Cite
|
Sign up to set email alerts
|

Self-Supervised Learning Based Anomaly Detection in Synthetic Aperture Radar Imaging

Abstract: In this paper, we proposed to investigate unsupervised anomaly detection in Synthetic Aperture Radar (SAR) images. Our approach considers anomalies as abnormal patterns that deviate from their surroundings without prior knowledge of their characteristics. This method deals with the crucial problems related to the presence of speckle, the spatial correlation structures in SAR images, and the lack of annotated data to train a detection algorithm. Our proposed method aims to address these issues through a self-su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 74 publications
(108 reference statements)
0
5
0
Order By: Relevance
“…A deep-learning self-supervised algorithm developed explicitly for SAR anomaly detection [8] is used to test the proposed RX self-supervision method. The standard L 1 loss function is replaced with the newly defined loss.…”
Section: Proposed Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A deep-learning self-supervised algorithm developed explicitly for SAR anomaly detection [8] is used to test the proposed RX self-supervision method. The standard L 1 loss function is replaced with the newly defined loss.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…An ablation study is realized to test the apport of the new loss. The architecture is the same as the one described in [8]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Letting these kernels be trainable could enhance the performance of classification and segmentation. Furthermore, most despeckling techniques such as the one presented on Reference [49] can not be used as it only works for real-valued images.…”
Section: Coherency Vs Paulimentioning
confidence: 99%
“…In this study, I showed how amplitude data-derived scattering mechanisms can aid in sinkhole-related anomaly detection. Auto-encoder based methods, such as Adversarial Auto Encoder (AAE), have been used for anomaly detection in amplitude image [128]. I recommend that phase-related anomaly detection methods used in Chapter 5 should be combined with self-supervised anomaly detection meth-…”
Section: • Further Use Of Amplitude Data In Anomaly Detectionmentioning
confidence: 99%